Pruritic cutaneous lesions on the chest - Inês Zão; Carla Matias (Sociedade Galega de Medicina Interna, 2019)
We present the case of an 82 years old woman with history of Diabetes mellitus type 2 and arterial hypertension, chronically medicated with insulin glargine 20 units/day and amlodipine/ valsartan 5/160 mg per day. The patient was admitted to the emergency department due to dyspnea and chest pain with 1 day evolution, reporting also a 3-months history of asthenia and pruritic cutaneous lesions on the chest. On admission the patient was pale, polypneic and tachycardic with erythematous cutaneous lesions localized on the anterior and posterior thoracic region.